2016
DOI: 10.1186/s12933-016-0475-5
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of cardiometabolic parameters in non-smokers, current smokers, and quitters in diabetes: a systematic review and meta-analysis

Abstract: BackgroundSmoking is associated with increased macrovascular and microvascular complications in people with diabetes. In addition to other concomitant vascular perturbations, it also seems to influence the cardiometabolic parameters, which may partly explain the accelerated rate of vascular complications in smokers with diabetes. While smoking cessation is advocated as a universal component of the management of diabetes, there is some anecdotal evidence that HbA1c could increase following smoking cessation. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 52 publications
2
45
2
1
Order By: Relevance
“…Recent data show tobacco use is higher among adults with chronic conditions (164) as well as in adolescents and young adults with diabetes (165). Smokers with diabetes (and people with diabetes exposed to second-hand smoke) have a heightened risk of CVD, premature death, microvascular complications, and worse glycemic control when compared with nonsmokers (166,167). Smoking may have a role in the development of type 2 diabetes (168-171).…”
Section: Diabetic Kidney Diseasementioning
confidence: 99%
“…Recent data show tobacco use is higher among adults with chronic conditions (164) as well as in adolescents and young adults with diabetes (165). Smokers with diabetes (and people with diabetes exposed to second-hand smoke) have a heightened risk of CVD, premature death, microvascular complications, and worse glycemic control when compared with nonsmokers (166,167). Smoking may have a role in the development of type 2 diabetes (168-171).…”
Section: Diabetic Kidney Diseasementioning
confidence: 99%
“…There is almost no evidence for an association between HbA1c and respiratory disease. A metaanalysis of 14 observational studies with 98,978 participants (with diabetes) found that smokers had significantly higher HbA1c levels than non-smokers (Kar et al 2016). Only sparse information is available on the dose-response relationship between HbA1c and the smoking dose, determined for example by daily cigarette consumption (CPD), pack-years or suitable biomarkers of exposure such as cotinine in body fluids.…”
Section: Miscellaneous Biomarkersmentioning
confidence: 99%
“…The overall findings should be interpreted in the context of several potential limitations. First, plenty of studies reported lipid profiles are closely correlated with exercise (Igarashi & Nogami, 2019), diet (Chiu et al, 2016), and smoking (Kar et al, 2016). Unfortunately, these variables were not evaluated in most of the studies included, which may confound the overall findings.…”
Section: Limitationsmentioning
confidence: 99%